Glutathionylation of Pea Chloroplast 2-Cys Prx and Mitochondrial Prx IIF Affects Their Structure and Peroxidase Activity and Sulfiredoxin Deglutathionylates Only the 2-Cys Prx - Calderón, Aingeru; Lázaro-Payo, Alfonso; Iglesias-Baena, Iván; Camejo, Daymi; Lázaro, Juan J.; Sevilla, Francisca; Jiménez, Ana (Frontiers in Plant Science, 2017)
Together with thioredoxins (Trxs), plant peroxiredoxins (Prxs), and sulfiredoxins (Srxs) are involved in antioxidant defense and redox signaling, while their regulation by post-translational modifications (PTMs) is increasingly regarded as a key component for the transduction of the bioactivity of reactive oxygen and nitrogen species. Among these PTMs, S-glutathionylation is considered a protective mechanism against overoxidation, it also modulates protein activity and allows signaling. This study explores the glutathionylation of recombinant chloroplastic 2-Cys Prx and mitochondrial Prx IIF from Pisum sativum. Glutathionylation of the decameric form of 2-Cys Prx produced a change in the elution volume after FPLC chromatography and converted it to its dimeric glutathionylated form, while Prx IIF in its reduced dimeric form was glutathionylated without changing its oligomeric state. Mass spectrometry demonstrated that oxidized glutathione (GSSG) can glutathionylate resolving cysteine (Cys174), but not the peroxidatic equivalent (Cys52), in 2-Cys Prx. In contrast, GSSG was able to glutathionylate both peroxidatic (Cys59) and resolving (Cys84) cysteine in Prx IIF. Glutathionylation was seen to be dependent on the GSH/GSSG ratio, although the exact effect on the 2-Cys Prx and Prx IIF proteins differed. However, the glutathionylation provoked a similar decrease in the peroxidase activity of both peroxiredoxins. Despite growing evidence of the importance of post-translational modifications, little is known about the enzymatic systems that specifically regulate the reversal of this modification. In the present work, sulfiredoxin from P. sativum was seen to be able to deglutathionylate pea 2-Cys Prx but not pea Prx IIF. Redox changes during plant development and the response to stress influence glutathionylation/deglutathionylation processes, which may represent an important event through the modulation of peroxiredoxin and sulfiredoxin proteins.